Munshi Premchand: The Emperor Among Novelists - Gupta, Surendra Kumar (International Journal of Psychosocial Rehabilitation, 2013)
This paper attempts to study how Premchand, author of novels and short stories in Hindi and Urdu pioneered in adapting Indian themes to Western literary styles. Premchand (1880-1936) wrote about things that have always existed but had hitherto been considered beyond the pale of literature – exploitation and submission, greed and corruption, the straight jacket of poverty and an unyielding caste system. Son of a post office clerk, he was named Dhanpat Rai (literally meaning the ‘master of wealth’), yet he waged a lifelong battle against unremitting genteel poverty. Reading and writing, always the stock in trade of a good kayastha boy, coupled with acute social consciousness and an unerring eye for detail turned him – with a literary career spanning three decades which included 14 novels, 300 short stories, several translations from English classics, innumerable essays and editorial pieces – into a qalam ka sipahi, a ‘soldier with the pen’. In Premchand’s world, the bad are needed to offset the good. Self-seeking, bhang-drinking pandits, effete landlords, college-going newly-westernised sahibs and memsahibs, and corrupt petty officials are set against another set of characters. There is, for instance, the orphan Hamid who buys a pair of iron tongs for his grandmother instead of sweets and toys for himself, little Ladli who sets aside her share of puris for old Kaki, the corrupt Pandit Alopideen who shows immense generosity for a fallen but upright opponent, Jhuri who loved his oxen like his own children – all these help restore our faith that human beings can occasionally be good and kind too. Stock characters like Dukhi the tanner, Halku the peasant, Gangi the untouchable woman, Buddhu the shepherd, Bhajan Singh the hot-headed thakur and countless others served a useful purpose to someone of Premchand’s literary disposition: he exploited the intrinsic worth of stock characters and stock situations to portray a very real world. Like the Russian masters whom he admired so much, realism for Premchand was a mise en scene against which he built up the props of character and plot. “I write for only one sake: To present a human truth, or to show a new angle of looking at common things,” he wrote. A legendary figure in the space of Hindi and Urdu fiction, a social reformer and activist himself, his work went beyond entertainment and offered social criticism and was full of social purpose. Although some of his best work is a part of around 250 short stories compiled under the title Manasarovar, these are the five novels that embody the values and spirit he stood for and those that remain timeless, just as his writing.